Laryngeal Chondrosarcoma: Successful Use of Video Laryngoscope in Anticipated Difficult Airway Management - Vladimir Dolinaj; Sanja Milošev; Dušanka Janjević (Acta Clinica Croatica, 2016)
Laryngeal chondrosarcoma is a rare mesenchymal tumor, most frequently affecting cricoid cartilage. The objective of this report is to present successful video laryngoscope usage in a patient with anticipated difficult airway who refused awake fiberoptic endotracheal intubation (AFOI). A 59-year-old male patient was admitted in our hospital due to difficulty breathing and swallowing. On clinical examination performed by ENT surgeon, preoperative endoscopic airway examination (PEAE) could not be performed properly due to the patient’s uncooperativeness. Computed tomography revealed a spherical tumor that obstructed the subglottic area almost entirely. Due to the narrowed airway, the first choice for the anticipated difficult airway management was AFOI, which the patient refused. Consequently, we decided to perform endotracheal intubation with indirect laryngoscope using a C-MAC video laryngoscope (Karl Storz, Tuttlingen, Germany). Reinforced endotracheal tube (6.0 mm internal diameter) was placed gently between the tumor mass and the posterior wall of the trachea in the first attempt. Confirmation of endotracheal intubation was done by capnography. In a patient with subglottic area chondrosarcoma refusing PEAE and AFOI, video laryngoscope is a particularly helpful device for difficult airway management when difficult airway is anticipated.